Konsep Kehakiman dalam Islam - Ahmad, Mohd Nazri (Jurnal Usuluddin, 2001)
This article discusses the history of Islamic Judiciary mainly during the periods of the Prophet Muhammad (p.b.u.h), the Companions and Tabi'ins. It tries to elaborate how Islamic judicial system applied the criteria of electing judges, the scope of power and the acceptability of the post in Islam.